Adipose-derived stem/progenitor cells: roles in adipose tissue remodeling and potential use for soft tissue augmentation. (March 2009) - Yoshimura, Kotaro; Suga, Hirotaka; Eto, Hitomi
Many features of adipose tissue-specific stem/progenitor cells, such as physiological function and localization, have recently been examined. Adipose-tissue turnover is very slow and its perivascular progenitor cells differentiate into adipocytes in the next generation. The progenitor cells play important roles in physiological turnover, hyperplasia and atrophy of adipose tissue, as well as in incidental remodeling, such as postinjury repair. Adipose tissue has been used as an autologous filler for soft tissue defects, despite unpredictable clinical results and a low rate of graft survival, which may be due to the relative deficiency of progenitor cells in graft materials. A novel transplantation strategy, termed cell-assisted lipotransfer, involves the enrichment of adipose progenitor cells in grafts; preliminary results suggest this approach to be safe and effective.